Research on the Current Situation and Countermeasures of Regional Ecological Agriculture Development in Shaanxi Province - Jia, Qingyang (International Journal of Global Economics and Management, 2024)
The vigorous development of regional ecological agriculture in Shaanxi Province can effectively solve the problems of resource utilization and environmental protection, promote the adjustment of rural industrial structure and rural revitalization. In order to further promote the development of ecological agriculture in Shaanxi Province, this article focuses on the current situation of regional ecological agriculture development in Shaanxi Province, analyzes the problems existing in the development of regional ecological agriculture in Shaanxi Province, and conducts in-depth analysis from three levels: resource allocation, government supervision, and technological development. It explores the path of sustainable development of ecological agriculture and proposes effective measures to promote the healthy, harmonious, and sustainable development of ecological economy in Shaanxi Province. It also provides ideas and references for the development of ecological agriculture in other regions of China.